2022
DOI: 10.3947/ic.2021.0027
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of SARS-CoV-2-Positive Mothers and Their Newborns in Korea

Abstract: It is unclear how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) affects pregnant women and their fetuses or newborns. We report two infants born to mothers with coronavirus disease 2019 (COVID-19) in Korea. The first case was a healthy female baby born at 39 +3 weeks' gestation from a mother diagnosed with COVID-19. The second case was a female baby born at 38 +0 weeks' gestation. The newborn in the second case had symptoms of respiratory distress im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Among the studies decribing histological examination of placentas in the context of SARS-CoV-2 maternal infection (on Pubmed, with keywords “SARS-CoV-2” + “placenta” + “pathology”), which include three meta-analyses, poor fetal outcome has been frequently reported in association with the “placentitis triad”, consisting in intervillositis (with an acute or chronic infiltrate), excess fibrin deposition and trophoblastic necrosis [ Supplementary Table S1 ], refs. [ 3 , 4 , 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies decribing histological examination of placentas in the context of SARS-CoV-2 maternal infection (on Pubmed, with keywords “SARS-CoV-2” + “placenta” + “pathology”), which include three meta-analyses, poor fetal outcome has been frequently reported in association with the “placentitis triad”, consisting in intervillositis (with an acute or chronic infiltrate), excess fibrin deposition and trophoblastic necrosis [ Supplementary Table S1 ], refs. [ 3 , 4 , 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Summary of the placental lesions in reported cases of SARS-CoV-2 infection in the literature [ 3 , 4 , 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
mentioning
confidence: 99%
“…38,39 Current reports suggest that placental abnormalities do not predict fetal SARS-CoV-2 infection. 40,41 An elegant review by Komine-Aizawa et al showed that irrespective of neonatal COVID-19 positivity after birth, placental findings are seen in many pregnant women. Also, fetuses are not necessarily affected despite syncytiotrophoblasts being infected frequently.…”
Section: Outcomes Of Pregnant Mothers With Covid-19mentioning
confidence: 99%
“…A few studies have reported adverse neonatal outcomes of COVID-19 infected mothers; however, these associations are still unclear [ 7 , 8 , 12 ]. Currently, limited data with small sample sizes are available regarding the risk of perinatal infection and neonatal outcomes of infants born to COVID-19 infected mothers in Korea [ 1 , 13 , 14 ]. A recent Korean National Mother-Child Cohort study on neonatal outcomes discovered a possible association of COVID-19 mothers with increased NICU admission [ 15 ].…”
Section: Introductionmentioning
confidence: 99%